Implementasi Media Digital dalam Pengembangan Citra Positif Wakil DPRD Sumbar - Reza Prayogi; Emeraldy Chatra; Elva Ronaning Roem (Fakultas Ilmu Sosial dan Ilmu Poliitik Universitas Ichsan Gorontalo, 2026)
This study aims to analyze the role and implementation of digital media use by the Deputy Speaker of the West Sumatra Provincial DPRD in the context of political communication, while also examining the relevance of content to audience perceptions and satisfaction levels in building a positive image. Using a qualitative approach and case study method, this study examines in depth how the simultaneous use of digital media, particularly through Instagram, Facebook, and TikTok, influences public perception of the legislator. Research data was collected through interviews, field observations, and document analysis, then analyzed using Miles and Huberman's interactive analysis technique. The results show that although digital media has been utilized as a means of disseminating constitutional activities, its effectiveness in building a strong positive image still needs to be improved, especially in terms of transparency and public support. The type of content considered most effective is content that displays direct interactions between legislators and the public and shows the process of conveying public aspirations. Based on the analysis by admin Iqra Chissa, content with these characteristics is able to present a more humanistic and communicative image compared to content that displays formal activities such as meetings, regional visits, or hearings, which tend to be rigid and less engaging for the audience. However, there is still a perception that some content emphasizes political and personal interests over public interest. Therefore, content relevance that focuses on public needs and aspirations is crucial for increasing public satisfaction and trust.